Complete Genome Sequences of the Carlavirus Sweet potato chlorotic fleck virus from East Timor and Australia - Maina, Solomon (Genome Announc, 2016)
We present here the first complete genome sequences of Sweet potato chlorotic fleck virus (SPCFV) from sweet potato in Australia and East Timor, and we compare these with four complete SPCFV genomes from South Korea and one from Uganda. The Australian, East Timorese, South Korean, and Ugandan genomes differed considerably from each other.